2012
DOI: 10.1039/c2cs35022j
|View full text |Cite
|
Sign up to set email alerts
|

Excitation energy transfer in multiporphyrin arrays with cyclic architectures: towards artificial light-harvesting antenna complexes

Abstract: Since highly symmetric cyclic architecture of light-harvesting antenna complex LH2 in purple bacteria was revealed in 1995, there has been a renaissance in developing cyclic porphyrin arrays to duplicate natural systems in terms of high efficiency, in particular, in transferring excitation energy. This tutorial review highlights the mechanisms and rates of excitation energy transfer (EET) in a variety of synthetic cyclic porphyrin arrays on the basis of time-resolved spectroscopic measurements performed at bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(142 citation statements)
references
References 61 publications
0
141
0
1
Order By: Relevance
“…[88][89][90] Schugar and coworkers reported that a cyclic array of hexameric Zn-porphyrin 30 6 formed through head-to-tail nitrogen-to-zinc coordination in a single crystal, although a self-coordinating dimer 30 2 was assembled in solution (Scheme 15). 91 So far, the control of the internal angle of ligand-appended porphyrin has rarely been successful in designing large macrocyclic wheels.…”
Section: Organization Of Multiporphyrin Wheelsmentioning
confidence: 97%
See 1 more Smart Citation
“…[88][89][90] Schugar and coworkers reported that a cyclic array of hexameric Zn-porphyrin 30 6 formed through head-to-tail nitrogen-to-zinc coordination in a single crystal, although a self-coordinating dimer 30 2 was assembled in solution (Scheme 15). 91 So far, the control of the internal angle of ligand-appended porphyrin has rarely been successful in designing large macrocyclic wheels.…”
Section: Organization Of Multiporphyrin Wheelsmentioning
confidence: 97%
“…The experimental procedures, how to evaluate and analyze the experimental results, and covalently linked porphyrin arrays are welldocumented in a review by Kim and coworkers. 89 A multichromophore array with energy cascade can direct sequential photoexcited energy flow. Weiss and coworkers arranged boron dipyrromethene (BOD-IPY)-Zn porphyrin-free base porphyrin as an energy cascade array 91·92 based on a phenanthroline-strapped porphyrin, which recognizes an imidazolyl group inside the strap.…”
Section: B Sequential Energy Transfer In Multiporphyrin Arraysmentioning
confidence: 99%
“…1 This stimulates researchers to synthesis cyclic porphyrin arrays to achieve high EET efficiency. 32,33 …”
Section: Seriesmentioning
confidence: 99%
“…However, this also restricts the conjugation length and therefore is not the best solution for certain applications 12 . For an efficient “through bond” charge transport, it is preferable that the porphyrin rings show an extended π-orbital communication (conjugation) 13 .…”
Section: Introductionmentioning
confidence: 99%